Strategic innovation : embedding innovation as a core competency in your organization - Snyder, Nancy Tennant, 1957- (Jossey-Bass business & management series., 2003)
Strategic Innovation offers a flexible, customizable template that managers, executives, and business leaders can use to introduce an effective innovation strategy throughout their organization. The authors, Nancy Tennant Snyder and Deborah L. Duarte, provide the tools needed to craft a workable strategy for embedding innovation as a core competency across an enterprise. Instead of innovation for innovation's sake, the authors offer a proven business-focused way to change a culture from point-in-time innovations from a few to a continuous pipeline of innovations from everywhere and everyone. Ba.